2021
DOI: 10.48550/arxiv.2103.14733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Strong Magnetic Fields on the Hadron-Quark Deconfinement Transition

Betânia C. T. Backes,
Kauan D. Marquez,
Débora P. Menezes

Abstract: The aim of the present work is to investigate the effects of strong magnetic fields on the hadronquark phase transition point at zero temperature. To describe the hadronic phase, a relativistic mean field (RMF) model is used and to describe the quark phase a density dependent quark mass model (DDQM) is employed. As compared with the results obtained with non-magnetised matter, we observe a shift of the transition point towards higher pressures and, generally also towards higher chemical potentials. An investig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…As can be seen from the figure, a strong magnetic field pushes the onset of quark matter to higher densities and pressures, thus further delaying the appearance of a potential quark core in neutron stars. In other studies, it is found in a similar way that a strong magnetic field shifts the transition to quark matter to higher densities, see the review [51], too.…”
Section: Effect On the Equation Of Statementioning
confidence: 54%
“…As can be seen from the figure, a strong magnetic field pushes the onset of quark matter to higher densities and pressures, thus further delaying the appearance of a potential quark core in neutron stars. In other studies, it is found in a similar way that a strong magnetic field shifts the transition to quark matter to higher densities, see the review [51], too.…”
Section: Effect On the Equation Of Statementioning
confidence: 54%